Camponeses e capitalistas no lugar Entre Ribeiros - Paracatu/MG - Oliveira, Pedro Machado de (2018)
The proposal of this research stems from observations made in the territories constituted by settlers and peasants in Entre Ribeiros, a rural region of the city of Paracatu, State of Minas Gerais (MG), Brazil. The study area had been predominantly used for extensive livestock production until the 1970s, but changes began to emerge from 1980 onwards, when a colonization project named Projeto de Colonização Paracatu Entre Ribeiros was implemented in the region. In total, there are more than 31,000 hectares of flat lands in Paracatu, where agribusiness thrives due to the great appropriation of local resources: land and water. The irrigation is possible thanks to the abundance of water in Entre Ribeiros stream and in Paracatu river, what allows up to three annual plantings. There, grains are grown, especially soybeans, corn and beans. However, in the last decade, there was an introduction and an advancement of sugarcane on the lands where grains are grown because of the implementation of a bioenergy station, Bioenergia do Vale do Paracatu Ltda (BEVAP), in the nearby city of João Pinheiro. Although the predominance of agribusiness in the region is clear, there is also the Assentamento Santa Rosa, a rural settlement project constituted of 65 plots, each one with 36.7 ha, where the settlers begin to develop a family economy deriving from the condition of plot owners. Besides dedicating themselves to milk production, they still produce leaf vegetables and fruits from which pulps are extracted and commercialized. Nonetheless, the autonomy was not reached by most of the settlers, since that the received plots did not have any infrastructure and with limited financial resources, they could not obtain enough income to support the family. Furthermore, there were some problems with the first crops, what forced the families to find a solution. These happenings intensified the financial difficulties, what turned out to be a decisive factor for their future: some of them, as a temporary solution, opted for working in neighbors' plots, whereas for others the solution was to abandon the land and request for the property transfer process. A few ones slowly started to product milk. It allowed their permanence in there, but they remained subordinated to the market, since the production requires a range of goods which are commercialized by a local cooperative.